Isolated Vastus Lateralis Rupture and Repair Using Suture Anchor Technique - Pierce Johnson; Ryan Digiovanni; Tony Nguyen (Case Reports in Orthopedics)
Introduction. This is a case report of an isolated vastus lateralis rupture identified by MRI and treated successfully with surgical repair. Case Presentation. A 50-year-old male recreational weightlifter who sustained an isolated vastus lateralis rupture while dead lifting and underwent surgical repair using a suture anchor fixation. Conclusion. An isolated vastus lateralis rupture is a rare injury that may be successfully treated with surgical repair allowing return to preinjury activities.